2019
DOI: 10.7759/cureus.5229
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamic Acidemia: An Underrecognized and Underdiagnosed Cause of High Anion Gap Metabolic Acidosis - A Case Report and Review of Literature

Abstract: Pyroglutamic acidemia (oxoprolinemia) is an underrecognized cause of high anion gap acidosis resulting from derangement in the gamma-glutamyl cycle. Pyroglutamic acidemia is most commonly diagnosed in the pediatric population in patients with inherited autosomal recessive enzyme deficiencies. However, acquired pyroglutamic acidemia can present in the adult population. Patients often present with confusion, nausea, and vomiting as well as an elevated anion gap metabolic acidosis. This article describes a case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Glutathione is important in maintaining a healthy redox state by serving as an antioxidant (Durante, 2019 ; Holeček, 2020 ; Lushchak, 2012 ). Our finding of an inverse association between markers of arterial stiffness with pyroglutamic acid levels, an intermediate of the y-glutamyl cycle, along with the precursors for glutathione, may suggest that more amino acids may be made available to produce glutathione (Durante, 2019 ; Gueta et al, 2020 ; Lushchak, 2012 ; Venkataraman et al, 2019 ), possibly due to increased oxidative stress. As stated above, we indicated elevated ROS levels in the CVD risk group.…”
Section: Discussionmentioning
confidence: 88%
“…Glutathione is important in maintaining a healthy redox state by serving as an antioxidant (Durante, 2019 ; Holeček, 2020 ; Lushchak, 2012 ). Our finding of an inverse association between markers of arterial stiffness with pyroglutamic acid levels, an intermediate of the y-glutamyl cycle, along with the precursors for glutathione, may suggest that more amino acids may be made available to produce glutathione (Durante, 2019 ; Gueta et al, 2020 ; Lushchak, 2012 ; Venkataraman et al, 2019 ), possibly due to increased oxidative stress. As stated above, we indicated elevated ROS levels in the CVD risk group.…”
Section: Discussionmentioning
confidence: 88%
“…Benjamini–Hochberg correction ( q value) - ∗ q ≤ 0.05; ∗∗ q ≤ 0.001. Grouping: obese group ( N = 196) – at least 0.55 waist-to-height ratio; physically inactive group ( N = 608) – less than 150 min moderate intensity/less than 75 min vigorous intensity/less than 600 MET-min moderate–vigorous intensity; smoking group ( N = 363) – at least 11 ng/ml cotinine and self-reported smoking; Excessive alcohol intake group [66] – at least 49 U/l GGT and self-reported drinking; masked hypertensive group ( N = 206) – normal clinic BP and 24 h/day/night BP classified as hypertensive; hyperglycaemic group ( N = 119) – at least 5.7% HbA1c; dyslipidemic group ( N = 191) – greater than 3.4 mmol/l LDL; low socioeconomic group ( N = 477). Metabolite concentration expressed as arbitrary units.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione is important in maintaining a healthy redox state by serving as an antioxidant [62][63][64]. Our finding of more abundant levels of pyroglutamic acid levels, along with the more abundant levels of various precursors of the y-glutamyl cycle, such as glutamine, cystine, glycine, methionine and serine may suggest a dysregulated y-glutamyl cycle [62,63,65,66], possibly because of increased oxidative stress. In fact, we also indicated that GGT, total glutathione and ROS levels were elevated in respective risk groups and when risk factors are clustered together.…”
Section: Oxidative Stressmentioning
confidence: 93%
“…This depletion can result in decreased efficiency in the gamma-glutamyl cycle, similar to what is seen in individuals with pyroglutamic acidemia, which is a metabolic disorder characterized by a buildup of pyroglutamic acid in the body [ 25 ]. Accumulation of these metabolites is associated with chronic metabolic acidosis, neonatal hemolytic anemia, and variable neurological impairments such as mental impairment and spasticity [ 25 , 26 ]. Remarkably, the patient did have neonatal hemolytic anemia, as signified by the high reticulocyte count and neurological impairment, further suggesting a potential connection between the metabolic profile and the observed phenotype.…”
Section: Discussionmentioning
confidence: 99%